Analysis of Factors Causing Academic Procrastination in Students with Academic Achievements - Yana, Riri Sri; Yendi, Frischa Meivilona (Universitas Negeri Padang, 2023)
Procrastination still occurs in the world of education, including in students who excel. Students tend to procrastinate in doing assignments and prefer to participate in other activities. Factors that cause academic procrastination are: (1) internal factors, namely: factors that come from within the individual, and (2) external factors, namely: factors that come from outside the individual. This study aims to describe the factors that cause academic procrastination in students who excel academically at SMPN 30 Padang. The results showed that the factors behind the high procrastination of doing assignments in students who excel academically are: (1) internal factors are in the low category with a percentage of 36%, (2) external factors are in the medium category with a percentage of 36%. Based on the results of this study, guidance and counseling services that can be provided to reduce academic procrastination to students who excel academically are content mastery services, individual counseling services, and group guidance services.